Energy metabolism and muscle activation heterogeneity explain (Formula presented.) slow component and muscle fatigue of cycling at different intensities - do Nascimento Salvador, Paulo Cesar; Nascimento, Eduardo Marcel Fernandes; Antunes, Diego; Guglielmo, Luiz Guilherme Antonacci; Denadai, Benedito Sérgio [UNESP] (Wiley, 2023)
New Findings: What is the central question of this study? What are the physiological mechanisms underlying muscle fatigue and the increase in the O2 cost per unit of work during high-intensity exercise? What is the main finding and its importance? Muscle fatigue happens before, and does not explain, the (Formula presented.) slow component ((Formula presented.)), but they share the same origin. Muscle activation heterogeneity is associated with muscle fatigue and (Formula presented.). Knowing this may improve training prescriptions for healthy people leading to improved public health outcomes. Abstract: This study aimed to explain the (Formula presented.) slow component ((Formula presented.)) and muscle fatigue during cycling at different intensities. The muscle fatigue of 16 participants was determined through maximal isokinetic effort lasting 3 s during constant work rate bouts of moderate (MOD), heavy (HVY) and very heavy intensity (VHI) exercise. Breath-by-breath (Formula presented.), near-infrared spectroscopy signals and EMG activity were analysed (thigh muscles). (Formula presented.) was higher during VHI exercise (∼70% vs. ∼28% of (Formula presented.) reserve in HVY). The deoxygenated haemoglobin final value during VHI exercise was higher than during HVY and MOD exercise (∼90% of HHb physiological normalization, vs. ∼82% HVY and ∼45% MOD). The muscle fatigue was greater after VHI exercise (∼22% vs. HVY ∼5%). There was no muscle fatigue after MOD exercise. The greatest magnitude of muscle fatigue occurred within 2 min (VHI ∼17%; HVY ∼9%), after which it stabilized. No significant relationship between (Formula presented.) and muscle force production was observed. The τ of muscle (Formula presented.) was significantly related (R2 = 0.47) with torque decrease for VHI. Type I and II muscle fibre recruitment mainly in the rectus femoris moderately explained the muscle fatigue (R2 = 0.30 and 0.31, respectively) and the (Formula presented.) (R2 = 0.39 and 0.27, respectively). The (Formula presented.) is also partially explained by blood lactate accumulation (R2 = 0.42). In conclusion muscle fatigue and O2 cost seem to share the same physiological cause linked with a decrease in the muscle (Formula presented.) and a change in lactate accumulation. Muscle fatigue and (Formula presented.) are associated with muscle activation heterogeneity and metabolism of different muscles activated during cycling.
Keywords: efficiency; muscle fatigue; oxidative metabolism; oxygen extraction; oxygen uptake slow component